Respostas

A melhor resposta!
  • Usuário do Brainly
2014-07-19T16:29:25-03:00
 \frac{ x^{2} -2}{ x^{2} -4} +2= x^{2}

mmc=x²-4

 x^{2} -2+2( x^{2} -4)= x^{2} ( x^{2} -4)

  x^{2} -4+2 x^{2} -8=  x^{4} -4 x^{2}

 x^{4} -7 x^{2} +12=0

 x^{2} =y

 y^{2} -7y+12=0

Δ=49-48
Δ=1
√Δ=1

 y^{'} = \frac{7+1}{2} = \frac{8}{2} =4

 y^{"} = \frac{7-1}{2} = \frac{6}{2} =3

como   x^{2} =y

 x^{2} =4

x'=2         
x"=-4

 x^{2} =y"

 x^{2} = \sqrt{3}

x'=√3

x"=-√3

S={-2,-√3,√3,2}


1 5 1
é só isso?
Acha pouco?
naao, muito obrigado está ótimo ;)